Pruning effects on ring width and wood hydrosystem of Prosopis flexuosa DC from arid woodlands - Giantomasi, María Alejandra; Alvarez, Juan Agustín; Villagra, Pablo Eugenio; Debandi, Guillermo Oscar; Roig-Juñent, Fidel Alejandro (2018)
Pruning is a silvicultural practice that could potentially improve the productivity in arid woodlands. However, there is not enough information about the influence of this practice on the tree-ring wood anatomy of desert Prosopis woodlands. We analyzed the effect of pruning trees of different diameter class (small and large, PDDC) and pruning intensity in small trees (heavy and intermediate, PDI). We evaluated tree-ring width, number of vessels, total vessel area, mean vessel size (total vessel area/number of vessels), vessel density (number of vessels/tree-ring area) and ratio of vessel area to tree-ring area in Prosopis flexuosa, a species widely used for firewood and poles in arid and semiarid areas of South America. For PDDC, trees were pruned during the winter of 2003, for which we focused on the period between 1995 and 2010 (8 years before and after pruning, respectively) and for PDI, trees were pruned during the winter of 2004, and we focused on the period between 1997 and 2010 (7 years before and after pruning, respectively). The data was analysed using Mixed Models. We observed that, small trees had a greater response to pruning than large individuals. In this sense, pruning increased radial growth (F2,247 = 6.08, p ≤ 0.01) and number of vessels (F2,247 = 6.36, p ≤ 0.01), and decreased the mean vessel size (F2,247 = 6.91, p ≤ 0.001) and ratio of vessel area to tree-ring area (F2,247 = 4.84, p ≤ 0.01) in small trees. Moreover, the response depended on pruning intensity, which was more evident in intermediate pruning. The increase in the vessel number and the decrease in mean vessel size observed in small trees denoted that pruning induces the generation of new, small-diameter vessels. This is considered a strategy to protect the water-conducting system in response to pruning. Studies at the anatomical level conducted in the present research revealed in detail how pruning influences wood production and anatomical modifications, indicating the importance of conducting wood anatomical analyses on tree rings in order to refine interpretations of the effect of pruning on stem growth.